2010
DOI: 10.1097/gme.0b013e3181d88962
|View full text |Cite
|
Sign up to set email alerts
|

Desvenlafaxine and escitalopram for the treatment of postmenopausal women with major depressive disorder

Abstract: Among postmenopausal outpatients with MDD, there were no significant differences in the efficacy of desvenlafaxine and escitalopram based on primary efficacy analyses. The results do not support the overall hypothesis that the serotonin-norepinephrine reuptake inhibitor desvenlafaxine has an efficacy advantage for the treatment of MDD in postmenopausal women because, in this particular subgroup, desvenlafaxine failed to prove superiority over escitalopram. Safety and tolerability were comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…compared the efficacy and safety of desvenlafaxine and escitalopram in MDD with symptoms of anxiety in postmenopausal women, and the study demonstrated that there was no significant difference in their efficacy as evaluated on HAM-D17 scores. [15] Desvenlafaxine treatment achieved ≥50% response in 56-58% (HAM-D Score) and 41-48% (HAM-A Score) of patients. Our study achieved a higher response rate, 73.68% in HAM-D score and 73.7% in HAM-A score.…”
Section: Discussionmentioning
confidence: 99%
“…compared the efficacy and safety of desvenlafaxine and escitalopram in MDD with symptoms of anxiety in postmenopausal women, and the study demonstrated that there was no significant difference in their efficacy as evaluated on HAM-D17 scores. [15] Desvenlafaxine treatment achieved ≥50% response in 56-58% (HAM-D Score) and 41-48% (HAM-A Score) of patients. Our study achieved a higher response rate, 73.68% in HAM-D score and 73.7% in HAM-A score.…”
Section: Discussionmentioning
confidence: 99%
“…In an 8-week study that included a duloxetine reference treatment arm, adjusted mean change from baseline to final evaluation for HAM-D 17 total scores was similar in magnitude for desvenlafaxine 50 mg (-9.8) and 100 mg (-10.5; p = 0.028 vs placebo -8.7) and duloxetine 60 mg (-10.3; p = 0.047 vs placebo) [38]. Flexible dose desvenlafaxine and escitalopram did not differ significantly on the primary efficacy end point (change in HAM-D 17 total score) in the acute (8 week) or continuation phases of a 26-week study of postmenopausal women with MDD [39]. Three randomized, placebo-controlled studies have evaluated the efficacy of desvenlafaxine 50 mg/day [31,32,38].…”
Section: Clinical Efficacy and Safetymentioning
confidence: 95%
“…[8] Overall, the study failed to demonstrate greater efficacy of desvenlafaxine compared to escitalopram during double-blind treatment in either phase [8] and, therefore, did not support the overall hypothesis that menopausal status (i.e. A randomized, comparator-controlled, multicentre trial evaluated the efficacy, safety and tolerability of desvenlafaxine versus escitalopram in postmenopausal outpatients with MDD.…”
Section: Introductionmentioning
confidence: 93%